Microbiome assembly in thawing permafrost and its feedbacks to climate - Jessica G. Ernakovich; Robyn A. Barbato; Virginia I. Rich; Christina Schädel; Rebecca E. Hewitt; Stacey J. Doherty; Emily D. Whalen; Benjamin W. Abbott; Jiri Barta; Christina Biasi; Chris L. Chabot; Jenni Hultman; et al. (Global Change Biology, 2022)
The physical and chemical changes that accompany permafrost thaw directly influence the microbial communities that mediate the decomposition of formerly frozen organic matter, leading to uncertainty in permafrost–climate feedbacks. Although changes to microbial metabolism and community structure are documented following thaw, the generality of post‐thaw assembly patterns across permafrost soils of the world remains uncertain, limiting our ability to predict biogeochemistry and microbial community responses to climate change. Based on our review of the Arctic microbiome, permafrost microbiology, and community ecology, we propose that Assembly Theory provides a framework to better understand thaw‐mediated microbiome changes and the implications for community function and climate feedbacks. This framework posits that the prevalence of deterministic or stochastic processes indicates whether the community is well‐suited to thrive in changing environmental conditions. We predict that on a short timescale and following high‐disturbance thaw (e.g., thermokarst), stochasticity dominates post‐thaw microbiome assembly, suggesting that functional predictions will be aided by detailed information about the microbiome. At a longer timescale and lower‐intensity disturbance (e.g., active layer deepening), deterministic processes likely dominate, making environmental parameters sufficient for predicting function. We propose that the contribution of stochastic and deterministic processes to post‐thaw microbiome assembly depends on the characteristics of the thaw disturbance, as well as characteristics of the microbial community, such as the ecological and phylogenetic breadth of functional guilds, their functional redundancy, and biotic interactions. These propagate across space and time, potentially providing a means for predicting the microbial forcing of greenhouse gas feedbacks to global climate change.

An arctic community of symbiotic fungi assembled by long‐distance dispersers: phylogenetic diversity of ectomycorrhizal basidiomycetes in Svalbard based on soil and sporocarp DNA - József Geml; Ina Timling; Clare H. Robinson; Niall Lennon; H. Chad Nusbaum; Christian Brochmann; Machiel E. Noordeloos; D. Lee Taylor (Journal of Biogeography, 2012)
Aim Current evidence from temperate studies suggests that ectomycorrhizal (ECM) fungi require overland routes for migration because of their obligate symbiotic associations with woody plants. Despite their key roles in arctic ecosystems, the phylogenetic diversity and phylogeography of arctic ECM fungi remains little known. Here we assess the phylogenetic diversity of ECM communities in an isolated, formerly glaciated, high arctic archipelago, and provide explanations for their phylogeographic origins. Location Svalbard. Methods We generated and analysed internal transcribed spacer (ITS) nuclear ribosomal DNA sequences from both curated sporocarp collections (from Svalbard) and soil polymerase chain reaction (PCR) clone libraries (from Svalbard and the North American Arctic), compared these with publicly available sequences in GenBank, and estimated the phylogenetic diversity of ECM fungi in Svalbard. In addition, we conducted coalescent analyses to estimate migration rates in selected species. Results Despite Svalbard’s geographic isolation and arctic climate, its ECM fungi are surprisingly diverse, with at least 72 non‐singleton operational taxonomic units (soil) and 109 phylogroups (soil + sporocarp). The most species‐rich genera are Thelephora / Tomentella , Cortinarius and Inocybe , followed by Hebeloma , Russula , Lactarius , Entoloma , Sebacina , Clavulina , Laccaria , Leccinum and Alnicola . Despite the scarcity of available reference data from other arctic regions, the majority of the phylogroups (73.4%) were also found outside Svalbard. At the same time, all putative Svalbard ‘endemics’ were newly sequenced taxa from diverse genera with massive undocumented diversity. Overall, our results support long‐distance dispersal more strongly than vicariance and glacial survival. However, because of the high variation in nucleotide substitution rates among fungi, allopatric persistence since the Pliocene, although unlikely, cannot be statistically rejected. Results from the coalescent analyses suggest recent gene flow among different arctic areas. Main conclusions Our results indicate numerous recent colonization events and suggest that long‐distance, transoceanic dispersal is widespread in arctic ECM fungi, which differs markedly from the currently prevailing view on the dispersal capabilities of ECM fungi. Our molecular evidence indicates that long‐distance dispersal has probably played a major role in the phylogeographic history of some ECM fungi in the Northern Hemisphere. Our results may have implications for studies on the biodiversity, ecology and conservation of arctic fungi in general.

Molecular phylogenetic biodiversity assessment of arctic and boreal ectomycorrhizal Lactarius Pers. (Russulales; Basidiomycota) in Alaska, based on soil and sporocarp DNA - JÓZSEF GEML; GARY A. LAURSEN; INA TIMLING; JACK M. MCFARLAND; MICHAEL G. BOOTH; NIALL LENNON; CHAD NUSBAUM; D. LEE TAYLOR (Molecular Ecology, 2009)
Despite the critical roles fungi play in the functioning of ecosystems, especially as symbionts of plants and recyclers of organic matter, their biodiversity is poorly known in high‐latitude regions. In this paper, we discuss the molecular diversity of one of the most diverse and abundant groups of ectomycorrhizal fungi: the genus Lactarius Pers. We analysed internal transcribed spacer rDNA sequences from both curated sporocarp collections and soil polymerase chain reaction clone libraries sampled in the arctic tundra and boreal forests of Alaska. Our genetic diversity assessment, based on various phylogenetic methods and operational taxonomic unit (OTU) delimitations, suggests that the genus Lactarius is diverse in Alaska, with at least 43 putative phylogroups, and 24 and 38 distinct OTUs based on 95% and 97% internal transcribed spacer sequence similarity, respectively. Some OTUs were identified to known species, while others were novel, previously unsequenced groups. Non‐asymptotic species accumulation curves, the disparity between observed and estimated richness, and the high number of singleton OTUs indicated that many Lactarius species remain to be found and identified in Alaska. Many Lactarius taxa show strong habitat preference to one of the three major vegetation types in the sampled regions (arctic tundra, black spruce forests, and mixed birch‐aspen‐white spruce forests), as supported by statistical tests of UniFrac distances and principal coordinates analyses (PCoA). Together, our data robustly demonstrate great diversity and nonrandom ecological partitioning in an important boreal ectomycorrhizal genus within a relatively small geographical region. The observed diversity of Lactarius was much higher in either type of boreal forest than in the arctic tundra, supporting the widely recognized pattern of decreasing species richness with increasing latitude.